Post-soviet transformations of public spaces in Lithuania: cases of Žirmūnai and Lazdynai residential districts - Grunskis, Tomas; Šiupšinskas, Matas (Journal of Architecture and Urbanism, 2012)
The article deals with the question of public space transformations during the last two decades in Lithuania. It is the part of broader research of the topic. Authors focus on the issue of main public spaces in Žirmūnai and Lazdynai residential districts in Vilnius, which are under the process of structural and spatial development. The article also analizes the problem of post-Soviet urban space quality and its transformations, as well as raises the question of preservation practices of urban (modernistic) heritage from the Soviet period. Authors analize and expose systems of public spaces and their hierarchy in these districts, which have been created according to modernistic principles and now are considered as highly valuable. Structural, compositional, functional and spacial developments of these spaces are analized in detail evaluating negative impact of such developments on the quality of modernistic urban space. Article in Lithuanian. Tarybinio laikotarpio viešųjų erdvių transformacijos Lietuvoje. Vilniaus Žirmūnų ir Lazdynų atvejis Santrauka. Straipsnyje aptariama tarybinio laikotarpio viešųjų erdvių kaita per pastarąjį dvidešimtmetį. Jame telkiamas dėmesys į Vilniaus Žirmūnų ir Lazdynų gyvenamųjų rajonų pagrindines viešąsias erdves bei jose esančius visuomeninius kompleksus. Tekste analizuojamos ir apibūdinamos tarybinio laikotarpio urbanistinės erdvės kokybinės kaitos ir urbanistinio paveldo teisinės apsaugos klausimas. Taip pat įvardijamos ir analizuojamos šių gyvenamųjų rajonų viešųjų erdvių sistemos bei jų elementų hierarchijos. Tekste detaliai analizuojama šių viešųjų erdvių kaita urbanistinės struktūros, tūrinės erdvinės kompozicijos ir funkciniu požiūriais. Keliama urbanistinės erdvės, kaip paveldo ir apsaugos objekto, problema. Reikšminiai žodžiai: urbanistinis paveldas, sovietmečio modernizmas, viešoji erdvė, LTSR gyvenamieji rajonai.